Transformasi Pembelajaran di Era Digital: Analisis Sosio-Antropologis Penggunaan Kecerdasan Buatan (AI) dalam Pendidikan (Systematic Literature Review (SLR)) - Bestari Ida Ayu Purnama; Sappirudin; I Putu Sriartha; I Wayan Mudana; I Made Pageh (Universitas Pendidikan Ganesha, 2025)
This article presents a Systematic Literature Review (SLR) on the use of Artificial Intelligence (AI) in education from a socio-anthropological perspective, with a specific focus on the context of Indonesia and Bali. The study aims to describe the development of AI integration in teaching and learning, analyze its socio-cultural impacts, identify research gaps, and formulate implications for educational policy and practice. The review shows that AI is utilized as a personal learning assistant, adaptive learning system, assessment automation tool, and learning analytics instrument. Its integration has triggered shifts in teachers’ knowledge authority, the formation of new learning habitus, the reproduction of digital inequalities, negotiations between technological modernity and local traditions, and changes in social interaction patterns in the classroom. The article proposes a conceptual framework of AI-based learning transformation and a learning syntax that is sensitive to Bali’s socio-cultural context. The findings highlight the importance of equitable infrastructure provision, AI literacy and ethics, strengthening teachers’ roles, and collaborative learning designs aligned with local cultural values.